Hubungan antara Aktivitas Fisik dan Depresi pada Remaja Sekolah Menengah Pertama - Rocky V. Pangerapan; Herdy Munayang; Bernabas H. R. Kairupan (Medical Scope Journal, 2023)
Abstract: Depression is a common mental disorder characterized by persistent sadness and loss of interest in many activities, accompanied by an inability to carry out daily activities for at least two weeks. This study aimed to analyze the relationship between physical activity and depression in junior high school adolescents. This was an observational and analytical study with a cross-sectional design conducted in all junior high school at Malalayang District in November 2022. Data collection technique used the Children Depression Inventory questionnaire (CDI) for depression and the International Physical Activity Questionnaire (IPAQ) for physical activity. The evaluation was grouped into none, mild, moderate, severe for depression, and mild, moderate, severe for physical activity. The results obtained 400 students as respondents. Most respondents had no depression with a total of 233 students (58%) and most respondents had a high level of physical activity with a total of 160 students (40%). The Chi-Square test obtained a p-value of 0.743 (p>0.05) for the relationship between level of depression and physical activity. In conclusion, there is no significant relationship between physical activity and depression in junior high school adolescents at Malalayang District. Keywords: junior high school students; adolescents; depression; physical activity   Abstrak: Depresi merupakan gangguan mental yang umum ditemukan ditandai dengan rasa sedih yang terus-menerus dan kehilangan minat melakukan aktivitas, disertai dengan ketidakmampuan melakukan aktivitas sehari-hari setidaknya selama dua minggu. Penelitian ini bertujuan untuk menganalisis hubungan antara aktivitas fisik dan depresi pada remaja SMP. Jenis penelitian ialah analitik observasional dengan desain potong lintang yang dilakukan pada seluruh Sekolah Menengah Pertama (SMP) di Kecamatan Malalayang pada bulan November 2022. Teknik pengumpulan data dengan menggunakan kuesioner Children Depression Inventory (CDI) untuk depresi dan International Physical Activity Questionnaire (IPAQ) untuk aktivitas fisik. Penilaiannya dikelompokkan dalam tidak ada, ringan, sedang, berat untuk depresi, serta ringan, sedang, berat untuk aktivitas fisik. Hasil penelitian mendapatkan 400 responden. Responden terbanyak memiliki tingkat depresi tidak ada dengan jumlah 233 siswa (58%) dan responden terbanyak memiliki tingkat aktivitas fisik tinggi dengan jumlah 160 siswa (40%). Uji statistik Chi-Square mendapatkan nilai p=0,743 (p>0,05) terhadap hubungan antara tingkat depresi dan aktivitas fisik. Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara aktivitas fisik dan depresi pada remaja SMP di Kecamatan Malalayang. Kata kunci: siswa Sekolah Menengah Pertama; remaja; depresi, aktivitas fisik